Drought monitoring in Ardabil province by means of SEPI fuzzy index developed based on the fuzzy logic - behroz Sobhani; ata gafarigilandeh; akbar goldost (تحقیقات کاربردی علوم جغرافیایی)
Drought defined as a climatic phenomenon with the humidity and rainfall shortage as compared with normal conditions. This phenomenon affects on all of aspects of human activities‌, severely. while, studies associated with this phenomenon on the basis of appropriate methods are very low. In the  present study, effort  has been made to analyze the drought state in Ardabil province by means of software system capabilities in MATLAB and SEPI index in two temporal scales of 6 and 12 months. The climatic data of synoptically stations of Ardabil were used, Parsabad and khalkhal countian in Ardabil province. Results of study show that SEPI index reflects the features of two SPI and SEI indices well. And also enters temperature in the studying of drought conditions as one of the effective parameters in changing of drought intensity. There‌fore, the investigation into drought with SEPI index is better than SPI index. Studies associated to drought on the basis of SEPI index shows that drought process is increasing in Ardabil province. Temperature also has an increasing flow with higher intensity. Longest temporal continuation of drought in province, has occurred in Parsabad station in temporal scale of 12 months, from June‌, 1998 to November, 1999 in 18 month period. The greatest percentage of drought occurrence is in Parsabad station and the minimum of that is observed in Khalkhal station.